2018
DOI: 10.1371/journal.pone.0198694
|View full text |Cite
|
Sign up to set email alerts
|

Stress cross-response of the antioxidative system promoted by superimposed drought and cold conditions in Coffea spp.

Abstract: The understanding of acclimation strategies to low temperature and water availability is decisive to ensure coffee crop sustainability, since these environmental conditions determine the suitability of cultivation areas. In this context, the impacts of single and combined exposure to drought and cold were evaluated in three genotypes of the two major cropped species, Coffea arabica cv. Icatu, Coffea canephora cv. Apoatã, and the hybrid Obatã. Crucial traits of plant resilience to environmental stresses have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
72
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(79 citation statements)
references
References 86 publications
(164 reference statements)
7
72
0
Order By: Relevance
“…These compounds normally complement the enzymatic defence system in detoxifying the ROS [39]. It has recently been shown that unlike the older counterparts, young coffee leaves have a poorly developed enzymatic antioxidant defence system and hence the reliance on oxidant scavenger compounds is inevitable [40,41]. In addition to defence, some phytochemicals in the current study have other functions in coffee plants.…”
Section: Discussionmentioning
confidence: 81%
“…These compounds normally complement the enzymatic defence system in detoxifying the ROS [39]. It has recently been shown that unlike the older counterparts, young coffee leaves have a poorly developed enzymatic antioxidant defence system and hence the reliance on oxidant scavenger compounds is inevitable [40,41]. In addition to defence, some phytochemicals in the current study have other functions in coffee plants.…”
Section: Discussionmentioning
confidence: 81%
“…The current results are in agreement with several reports were exogenous kinetin treatment increased the tolerance of plants to abiotic stress conditions through the increased activities of antioxidant enzymes [34][35][36]52], as well as the increased contents of several antioxidant compounds, such as flavonoids, gibberellins, salicylic acid, jasmonic acid and abscisic acid in salinity-stressed soybean plants [37], proline in drought-stressed rice [39], salvianolic acid and rosmarinic acid in Dracocephalum forrestii [40]. Although the accumulation of several secondary metabolites in the leaves of coffee plants under oxidative stress conditions is a well-known phenomenon [15,16], this study is the first to report a profound increment in the contents of these compounds in response to exogenous kinetin treatment under optimal or cold stress conditions. These secondary metabolites play a number of roles in the plant defense mechanisms against oxidative stress due to the presence of hydroxyl components and glycosylic linkages which scavenge the ROS, hence maintaining cellular homeostasis during oxidative stress conditions [21,[57][58][59].…”
Section: Discussionmentioning
confidence: 99%
“…That is, the superimposition of both cold and drought stress simultaneously reinforced the two antioxidative systems, while the enzymatic antioxidative systems was more reinforced during single exposure to drought than to cold stress. On the other hand, exposure to cold stress resulted in the accumulation of antioxidant compounds with less effect on the activities of the antioxidant enzymes [15]. Therefore, during cold stress conditions, while the nonenzymatic antioxidant system is more repressed, coffee plants rely on an alternative antioxidant system, which is made up of antioxidant compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Conilon under field conditions is delayed when the mean minimum temperature is < 17 ºC and > 31 ºC (Partelli et al 2010, Covre et al 2016. Such temperature extremes can negatively affect the physical plant traits, e.g., by reducing grain weight and yield (Ramalho et al 2018). An option to mitigate thermal stress on coffee is cultivation at higher altitudes; however, temperature drops to levels below 13 ºC/8 ºC (day/night) induce several metabolic alterations in Conilon coffee, with a negative impact on yield (Partelli et al 2009.…”
Section: Introductionmentioning
confidence: 99%